2020
DOI: 10.3389/fimmu.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Natural Killer Cell-Mediated Targeting of Sarcoma Through DNAM-1 and NKG2D

Abstract: Sayitoglu et al. Boosting NK Cell-Mediated Sarcoma Targeting cells was observed against the majority of tumor cell lines tested. In conclusion, DNAM-1 or NKG2D over-expression elicited a dynamic increase in NK cell degranulation against all sarcoma explants and cancer cell lines tested, including those that failed to induce a notable response in WT NK-92 cells. These results support the broad therapeutic potential of DNAM-1 + or NKG2D + GM NK-92 cells and GM human NK cells for the treatment of sarcomas and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 115 publications
3
37
0
Order By: Relevance
“…It was reported that the KLRK1 axis is becoming an emerging target in cancer immunotherapy [35,36], and the overexpression of CD226 or KLRK1 on NK cells resulted in e cient anti-sarcoma activity [37]. These studies were in accordance with our exploration to provide a molecular basis for the development of CD226-and KLRC4-KLRK1-targeted antitumor immune therapeutics.…”
Section: Discussionsupporting
confidence: 76%
“…It was reported that the KLRK1 axis is becoming an emerging target in cancer immunotherapy [35,36], and the overexpression of CD226 or KLRK1 on NK cells resulted in e cient anti-sarcoma activity [37]. These studies were in accordance with our exploration to provide a molecular basis for the development of CD226-and KLRC4-KLRK1-targeted antitumor immune therapeutics.…”
Section: Discussionsupporting
confidence: 76%
“…It was reported that the KLRK1 axis is becoming an emerging target in cancer immunotherapy [33,34], and the overexpression of CD226 or KLRK1 on NK cells resulted in e cient anti-sarcoma activity [35]. These studies were in accordance with our exploration to provide a molecular basis for the development of CD226-and KLRC4-KLRK1-targeted antitumor immune therapeutics.…”
Section: Discussionsupporting
confidence: 76%
“…10 Open access of these properties, NK cells are an attractive modality for cancer therapy since they can respond to diverse stimuli. 11 In addition, NK cells have shown evidence of activity against STS in both preclinical models [12][13][14] and clinical trials. 15 Despite some early success, however, the results of adoptive NK therapy in the treatment of solid tumors, including sarcomas, have been largely disappointing, 16 and dysfunction/diminished cytotoxicity in a pattern similar to T cell exhaustion has emerged as a barrier to successful translation of NK immunotherapy.…”
Section: Introductionmentioning
confidence: 99%